Synthesis N-Doped Activated Carbon from Sugarcane Bagasse for CO2 Adsorption - Kurniawan, Randy Yusuf; Oka, Irsandi Dwi; Atmaja, Lukman; Widiastuti, Nurul (IPTEK The Journal for Technology and Science, 2025)
Nitrogen-doped activated carbon (SBACN) was synthesized from sugarcane bagasse waste as acarbon source and urea as nitrogen source through potassium hydroxide (KOH) activation for 2 h at high temperature via two step methods. The synthesized SBCN was characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Fourier Transform Infrared (FTIR). The results showed that the SBCN has low degree crystallinity and graphitization with highly developed micropores due to synergistik activation effect of KOH and urea. These characteristics provide an important contribution to carbon dioxide adsorption capacity, which can reach up to 11,20% wt and this value is higher than pristine activated carbon. The results indicating that the presence of this nitrogen functionalities is found to have a beneficial influence on the carbon dioxide adsorption characteristic in standart condition and exhibit considerable potential in solid adsorption.